The ‘NeuroGate’: neuromorphic intelligence, extended mind, and neurorights. - Farina, Mirko; Lavazza, Andrea (Synthese, 2024)
This article discusses recent advancements in neurotechnologies and how they seem to support the Extended Mind Thesis (EMT), while also raising concerns about the mental integrity and privacy of individuals. In Sect. 1 we review recent research carried out at the frontiers of Brain Machine Interfaces (BMIs) and neuromorphic computing. Taking inspiration (Sect. 2) from research in these fields we present -with the help of some imagination- a futurist scenario of complete human-computer integration. We discuss a set of practical benefits and risks associated with the implementation of such a scenario, which -despite being fictional at the time of writing- is likely to be realized soon. We frame our discussion (Sect. 3) in the context of research conducted in the cognitive sciences on the extended mind thesis (EMT). We reflect on the epistemic and ontic aspects underlying such a scenario and argue that EMT finds supports in it. We further problematize (Sect. 4) around the significance of this envisaged scenario for research on neuro-rights. We therefore also discuss a series of ethical challenges related to their potential infringement. We conclude the paper (Sect. 5) by showing that the development of specific neurotechnologies can make the extension of the mind an increasingly pervasive and transformative phenomenon, while raising important concerns about the potential consequences for certain characteristics of individuals that may be crucial to preserve through the introduction of neurorights.